Supporting Homeownership and Naturalizing Debt<subtitle>The Housing Discourse in Swedish Newspapers 2005–2022</subtitle> - Chiara Valli; Neil Dunne (Nordic Journal of Urban Studies)
Today the Swedish housing market is at the heart of growing socioeconomic inequalities, due to the record high profits that could be made through “housing careers” in the past 20 years of upward housing prices. At the same time, rising household debt has been one of the major threats to financial stability. This situation clashes with the historical ambition to maintain tenure neutrality, i.e., the foundational principle on which Swedish housing policy has relied upon to provide adequate and affordable housing for all. Critical housing and political economy research have shown how, in the past three decades, housing, fiscal and legal reforms have consistently moved the Swedish housing system away from the tenure-neutrality principle in favor of homeownership. This study contributes to this literature by analyzing the discursive component of the process that has progressively eroded the social status of rent tenure compared to homeownership, focusing on the period 2005–2022. We analyze the media discourse around the Swedish housing market drawing on selected articles from the five main national newspapers. To gain insights into how ideological shifts within the housing market are constructed, we explain how homeownership, price rises, and debt have been normalized in public debate, and whose voices on these topics are given space in the Swedish media discourse.